Reestructuración técnico administrativa en la empresa Dicol LTDA (2017)
The accomplishment of the technician administrative restructure in the Dicol LTDA Company evaluates external factors and reorganize the internal ones. The diagnosis analyze the current organization using the self-diagnosis tool of the Bogota’s Trade Chamber. The technical study determinants the production process, optimization of resources and space such as the modification of his intermittent production line type to continues one. The administrative study established the organizational design, strategic planning and introduce a functions manual.